Cuyunon’s Familiarity of Traditional Folksongs and Dances: Its Educational and Sociological Significance - David R. Perez; Josephine M. Salmo; Susana P. Egger; Romelyn T. Dacanay; Lloyd Bancairen; Ferdinand C. Gelbolingo (Genius Journals, 2021)
The main purpose of the study is to determine the familiarity of the Cuyunons of today if they could still remember the traditional folksongs and dances of the municipality of Cuyo, Palawan. The study will also look into the educational and sociological significance of familiarity of these folksong and dances for the purpose of cultural revival, preservation and propagation of the Cuyonons’ rich culture. Descriptive research design was used in this study. Semi-structured researcher-made questionnaire was used in this study to gather data. The study was conducted in northern municipalities of Palawan which are dominated by Cuyunon natives. Samples were selected purposively by means of snowball method. Data collected were tallied and analyzed using descriptive statistics such as frequency counts, mean, and percentage. Majority of the respondents are aged 23-32 years old, female, single, at least high school graduate, government employee and full-blooded Cuyunon. Most of the respondents are still familiar with the Cuyunon folk songs and dances. These songs and dances should continue to be passed to next generation in order to revive and sustain our cultural heritage. The songs and dances which are not familiar to the young ones must be revived and continuously promoted to be familiarized by the young generation. These songs and dances are one of the symbols of the cultural heritage of the Cuyunon that must be treasured and lived always..
Keywords: preservation; familiarity; folksong; educational